2018
DOI: 10.1016/j.ejphar.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Diverse signalling of the platelet P2Y1 receptor leads to a dichotomy in platelet function

Abstract: Platelet P2Y receptor signalling via RhoGTPases is necessary for platelet-dependent leukocyte recruitment, where no platelet aggregation is observed. We investigated signalling cascades involved in distinct P2Y-dependent platelet activities in vitro, using specific inhibitors for phospholipase C (PLC) (U73122, to inhibit the canonical pathway), and RhoGTPases: Rac1 (NSC23766) and RhoA (ROCK inhibitor GSK429286). Human platelet rich plasma (for platelet aggregation) or isolated washed platelets (for chemotaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 67 publications
4
50
0
Order By: Relevance
“…Differences in the kinetics of platelet Akt, ERK1/2 and p38 phosphorylation in response to thrombin and to the inflammatory TLR2/1 receptor agonist lipopeptide Pam3CSK4 have been previously reported [22]. Moreover, we have previously shown that ADP stimulation triggering inflammatory events (pulmonary leukocyte recruitment) acts through activating the P2Y 1 receptors and small Rho GTPases Rac1 and RhoA [9,10], whilst it acts through the classical PLC pathway when triggering haemostatic responses, possibly as a result of differential molecular docking of endogenous agonists to the receptor [21]. However, those studies demonstrated the different signalling pathways induced by a single agonist leading to different platelet functional responses, and did not investigate the effect of different platelet stimuli on platelet responses.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
See 4 more Smart Citations
“…Differences in the kinetics of platelet Akt, ERK1/2 and p38 phosphorylation in response to thrombin and to the inflammatory TLR2/1 receptor agonist lipopeptide Pam3CSK4 have been previously reported [22]. Moreover, we have previously shown that ADP stimulation triggering inflammatory events (pulmonary leukocyte recruitment) acts through activating the P2Y 1 receptors and small Rho GTPases Rac1 and RhoA [9,10], whilst it acts through the classical PLC pathway when triggering haemostatic responses, possibly as a result of differential molecular docking of endogenous agonists to the receptor [21]. However, those studies demonstrated the different signalling pathways induced by a single agonist leading to different platelet functional responses, and did not investigate the effect of different platelet stimuli on platelet responses.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…18 trauma, where both haemostatic pathways and host defence are required [48]. Indeed, we and others have shown the requirement for some agents, including ADP, as a primer [39] necessary for robust platelet migration towards fMLP [21], and platelet-induced neutrophil chemotaxis towards MDC [9,21]. Further research is therefore warranted to investigate whether co-stimulation of platelets with low dose ADP and other inflammatory stimuli leads to potentiation of chemokine-induced platelet transmigration or other functions associated with inflammation.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
See 3 more Smart Citations